Diversity initiatives, status, and system-justifying beliefs: When and how diversity efforts de-legitimize discrimination claims. (July 2014) - Dover, Tessa L.; Major, Brenda; Kaiser, Cheryl R.
Diversity initiatives aim to improve outcomes for low-status groups in organizations. Yet they also may ironically act as legitimizing cues, leading to an assumption of fairness and reducing the detection of discrimination. We explored how group status (high-status majority vs. low-status minority) and beliefs about the fairness of the system influence when the mere presence of a diversity initiative will de-legitimize claims of discrimination against a company. Non-Hispanic Whites and Latino participants ( N = 135) read a profile of a company that had or had not received diversity awards, and then read a discrimination claim brought against the company by a Latino employee. Whites in general, and Latinos high in system-justifying beliefs, saw the company with diversity-awards as more respectful and fair to minorities than the company with neutral awards and also derogated the discrimination claimant more. Perceived fairness mediated the effect on claimant derogation. Implications are discussed.